Adequate Platelet Function Inhibition Confirmed by Two Inductive Agents Predicts Lower Recurrence of Ischemic Stroke/Transient Ischemic Attack. (24th August 2017) - Zhang, Lulu; Hu, Xiaowei; Zhu, Juehua; Cai, Xiuying; Kong, Yan; Wang, Hui; Diao, Shanshan; Zhao, Hongru; Jiang, Jianhua; Wang, Dapeng; Zhang, Quanquan; Qin, Yiren; et al.
Abstract : Background . The correlation between platelet function and recurrent ischemic stroke or TIA remains uncertain. Objective . To investigate two inductive agents to detect platelet functions and assess associations with recurrent ischemic stroke/TIA. Method . The study included 738 ischemic stroke/TIA patients. On days 0, 3, and 9 after antiplatelet therapy, platelet function tests were determined by maximum aggregation rate (MAR) using a PL-11 platelet function analyzer and phase matching reagents. Two induction agents were used: arachidonic acid (AA) and adenosine diphosphate (ADP). At 3-month follow-up, recurrence of stroke/TIA was recorded. Result . Cut-off values of adequate platelet function inhibition were MARADP < 35% and MARAA < 35%. Data showed that antiplatelet therapy could reduce the maximum aggregation rate. More importantly, adequate platelet function inhibition of either MARADP or MARAA was not associated with the recurrence of stroke/TIA, but adequate platelet function inhibition of not only MARADP but also MARAA predicts lower recurrence (0/121 (0.00%) versus 18/459 (3.92%), P = 0.0188). Conclusion . The platelet function tested by PL-11 demonstrated that adequate inhibition of both MARADP and MARAA could predict lower risk of ischemic stroke/TIA recurrence.